الأسس القانونية لحق الدول في الاستخدامات السلمية للطاقة النووية في القانون الدولي - بوبريق، علي يوسف (جامعة طبرق, 2022)
إن امتلاك الطاقة النووية السلمية حقا من حقوق الدول والشعوب، التي يصبغ عليها القانون الدولي العام المعاصر شرعيته ويفرض عليها حمايته، فهو حق قانوني مروع لكافة دول المجتمع الدولي دون تفرقة أو محاباة، مما دفع الدول لإصدار تشريعات وطنية تنظم استخدام الطاقة النووية سلميا داخلها. وقد تم إبرام عدة اتفاقيات دولية لتنظيم الاستخدامات السلمية للطاقة النووية. وقد شرعت مؤسسة الطاقة الذرية الليبية في مفاوضات مع عدد من الشركات العالمية المتخصصة في مجال بناء المفاعلات النووية لأغراض إنتاج الكهرباء وتحليه المياه. الأسس القانونية للاستخدامات السلمية للطاقة النووية في القانون الدولي: يستند حق الدول في الاستخدامات السلمية للطاقة النووية في القانون الدولي على مبدأ حق تقرير المصير الاقتصادي والسياسي الوارد في المادتين الأولى الفقرة الثانية والمادة الخامسة والخمسين من ميثاق الأمم المتحدة، كما أنه وارد في مواثيق كافة المنظمات الدولية الإقليمية، وحق الشعوب في تقرير مصيرها غير القابل للتصرف ومفاده تمتع الشعوب بحقها في السيادة التامة على جميع ما يتوفر لديها من ثروات وموارد طبيعية، ويستند أيضا على الحق في التنمية، وقد ورد هذا الحق بإعلان الحق في التنمية، اعتمد ونشر بموجب قرار الجمعية العامة للأمم المتحدة 128/41، 4/12/1986 م. Possession of nuclear energy for peaceful use purposes is a right of Countries and their peoples, which international laws give it legitimacy and protection. It is a legitimate legal right for all countries of the international community without discrimination or favoritisms. Which ledcountries to issue national legislation regulating the peaceful use of nuclear energy within them. Several international agreements have been concluded to regulate the peaceful uses of nuclear energy. The Libyan Nuclear Energy Corporation has started negotiations with several international companies specialized in building nuclear reactors for the purposes of electricity production and water desalination. Legal bases for the peaceful uses of nuclear energy in international law: The right of countries to the peaceful uses of nuclear energy is based on international law, on the principle of the right to economic and political self-determination “as mentioned in Articles 1, Paragraph 2, and Article 55 of the Charter of the United Nations, as well as contained in the charters of all regional and international organizations” and the inalienable right of peoples to self-determination that states that peoples have the right to full sovereignty over all their available natural wealth and resources.
Keywords: الطاقة النووية -- القوانين الدولية -- الاتفاقيات الدولية -- الأسلحة النووية -- القوانين والتشريعات